22 Supportive cardiology: an innovative practice model to integrate palliative care into the management of advanced heart failure. (9th April 2018) - Yu, Doris; Li, Polly; Fung, Erik; Yuen, Jacqueline; Woo, Jean; Chair, SY; Lee, Vivian; Choi, KC; Lo, Raymond
Abstract : Despite advances in evidence-based treatment to improve survivorship of patients with heart failure, the progressive deteriorating disease trajectory results in an expanding cohort of patients with advanced disease stage. Patients with advanced heart failure experience persistent physical and psychosocial symptoms despite optimal medical therapy. Frequent disease exacerbations require repeated hospitalisations, which heavily reduce the quality of life of patients and their families, and burden the healthcare system. The World Health Organisation advocates palliative care to improve the quality of life of patients with life-limiting diseases. However, palliative care is under-used in heart failure patients. Heart failure is characterised by its unpredictable progression and blurred boundaries between curative and palliative therapy. Therefore, international guidelines advocate an urgent need for a new care model to introduce supportive and palliative care early and gradually along the disease trajectory, overlapping and complementing active curative therapy. Preliminary research evidence is emerging to support the beneficial effects of palliative care interventions on symptom burden, quality of life and hospital service utilisation among patients with advanced heart failure. However, most of the studies focused on separate consultation by physicians or nurses, rather than an integrated heart failure and palliative care service, or providing transitional care in addition to the hospital-based palliative care service. There is no study examining the effects of integration of palliative care into heart failure management. A nurse-coordinated integrated heart failure-palliative care model is proposed.